A Comparative Sociomathematical Analysis of Student Pass Percentages in Two Educational Institutions - Brahma, Maneswar (Journal of Research in Vocational Education, 2025)
This study examines the statistical relationship between gender and locality in student pass percentages across two schools- one in a suburban area and another in a rural area-while considering gender-based variations in academic performance. A theoretical framework is developed to analyze the dependency of pass rates on gender and locality, categorizing conditions into four cases: gender- independent and locality-independent, gender-independent and locality-dependent, gender-dependent and locality-independent, and gender-dependent and locality-dependent. The findings suggest that gender and locality can significantly influence pass percentages, revealing potential disparities based on school location and student demographics. The study also introduces a theoretical model using proportionality assumptions to explore the probabilities of various academic outcomes. This framework can serve as a diagnostic tool for identifying biases in educational performance and guiding future policy interventions [1][2].